Good Medication Adherence and its Association with Meaning in Life among Thai Individuals with Schizophrenia - Teetharatkul, Teerapat; Pitanupong, Jarurin (Journal of Health Science and Medical Research, 2023)
Objective: To study medication adherence, meaning in life, the association of medication adherence and meaning in life among Thai individuals with schizophrenia. Material and Methods: This cross-sectional study surveyed all outpatient individuals with schizophrenia that followed up at the Psychiatric outpatient clinic, Songklanagarind Hospital. Three questionnaires were used:1) Demographic information 2) Medication adherence questionnaire and 3) The meaning in life questionnaire. Descriptive statistics were calculated using proportions, median and inter-quartile range (IQR) or mean and standard deviation (S.D.). Results: According to the study period; from December 2020 to March 2021, there were 110 respondents. Most of the respondents (94.5%) attended regular follow-ups, via doctor’ appointments. The majority of them were male (56.4%), single (76.4%), and Buddhist (82.7%). The mean age was 42.3+11.8 years. According to the medication adherence questionnaire, all participants (100%) had good medication adherence scores. Concerning meaning in life, most of the participants had high scores in all subparts of meaning in life; the presence of meaning in life and looking for something that made their lives feel purposeful and meaningful. There was no relationship between meaning in life scores and demographic characteristics (p-value>0.050). As all participants (100%) had good medication adherence scores, the association between medication adherence and meaning in life could not be established in this study. Conclusion: Most individuals with schizophrenia had good medication adherence as well as meaning in life. The search for meaning in life and meaning in taking medications may decrease negative medication attitudes and change the meaning of the illness.